Selected Philosophers’ Views of the Family - Szczap, Agnieszka (Uniwersytet Wrocławski, 2013)
The subject matter of this article is the history of philosophical speculation on the family. Philosophical reflections on the family date back to Antiquity. The main points of reference for the entire socio-philosophical literature are the views of Plato and Aristotle. Plato’s recognition of private property and the family as the main barriers in the way of a perfect state has weighed on all concepts of equality for many centuries. On the other hand, Aristotle, recognizing the family as the basic social group, place of formation of virtues and one of the conditions of a happy life, contributed to consolidate the view of the distribution of social roles based on sex as natural and necessary. Medieval philosophers placed the family in the perspective of creation, this life, and salvation. Modern philosophical concepts of thefamily were completely different and sometimes contradictory. On the one hand, there were ideas of such thinkers as John J. Rousseau, with emphasis on the polarization of education and social roles by gender, on the other, strongly egalitarian views of Mary Wollstonecraft. Feminist considerations of Simone de Beauvoire conclude the review of philosophical views on the family
Keywords: family; philosophy; domination; education; sex; gender; feminism